A three-dimensional plastic-damage model for polymer composite materials. (December 2022) - Cózar, I.R.; Otero, F.; Maimí, P.; González, E.V.; Miot, S.; Turon, A.; Camanho, P.P.
Abstract: A new 3D elastoplastic damage model is proposed to predict the plastic deformation and the progressive failure of unidirectional laminated composite materials at the meso-scale level. A non-associated flow rule is employed to properly define the volumetric plastic strains. The damage evolution laws are defined to account for the failure mechanisms on the longitudinal and transverse directions. Off-axis compressive and tensile tests with different ply orientations and high plastic dependency are used to demonstrate the ability of the model to capture the plastic response and the damage onset as well as the fracture planes. In addition, open-hole compressive and tensile tests with different dimensions are carried out to demonstrate the capability of the model to predict the failure strength. Good agreement is obtained between the numerical and experimental data.